The knowledge lift: The Swedish adult education program that aimed to eliminate low worker skill levels - James Albrecht; Gerard J van den Berg; Susan Vroman (Institute for Labour Market Policy Evaluation (IFAU), 2004)
The Swedish adult education program called Knowledge Lift is unprecedented in its size and scope, aiming to raise the skill level of all low-skilled workers towards the medium level. This paper evaluates the effects of program participation on individual labor market outcomes, notably employment and annual income, as well as on the labor market equilibrium. For the effects at the individual level we apply fixed effect methods allowing for treatment effect heterogeneity. The data are based on a number of matched longitudinal administrative data sets covering the full population of Sweden. For the equilibrium effects we analyze an equilibrium search model with heterogeneous worker skills. This model is calibrated using pre-program observations.
Keywords: I21; 330; Returns to education; training; program evaluation; wages; participation; unemployment; schooling; Swedish labour market; selectivity bias; treatment effect